Spectrum of Digestive Tract Diseases 1985-1987 at the Pediatric Gastroenterology Outpatient Clinic of Dr. Pirngadi General Hospital, Medan - Siregar, Charles Darwin; Sinuhaji, Atan Baas; Sutanto, A. H. (Paediatrica Indonesiana, 1990)
A retrospective study has been done on infants and children attending to the Pediatric Gastroenterology Outpatient Clinic of Dr.Pirngadi General Hospital in Medan, from 1985 through 1987. During the study there were 874 patients, 477 (54,58%) suffered from diarrhea, 209 (23,91%) had bloody stool, 20 (2,99%) jaundice, 57 (6,52%) abdominal pain, 48 (5,49%) abdominal distention, 30 (3,43%) vomiting, 13 (1,49%) constipation, and 20 (2,29%) others. Of all cases with diarrhoea, watery diarrhoea were found in only 319 (66,88%), diarrhoea with vomiting 84 (17,61%), and bloody diarrhoea 74 (15,51%). Stool examination in patients with diarrhoea revealed 144 (30,19%) cases with Candida albicans, while 16 (3,35%) of them with steatorrhoea. Of 63 patients with diarrhoea on which the clinitest had been performed, sugar intolerance were found in 30 (47,62%) cases.